The handbook of English for specific purposes - Paltridge, Brian; Starfield, Sue, 1952- (Chichester, West Sussex, UK : Malden, Ma. : Wiley-Blackwell, 2012)
Featuring a collection of newly commissioned essays, edited by two leading scholars, this Handbook surveys the key research findings in the field of English for Specific Purposes (ESP). Provides a state-of-the-art overview of the origins and evolution, current research, and future directions in ESP Features newly-commissioned contributions from a global team of leading scholars Explores the history of ESP and current areas of research, including speaking, reading, writing, technology, and business, legal, and medical English Considers persp.
pt. I. ESP and language skills -- pt. II. Areas of ESP research -- pt. III. ESP and pedagogy -- pt. IV. Research perspectives and methodologies in ESP research.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: English language -- Study and teaching; English language -- Study and teaching; EDUCATION -- Elementary; English language -- Study and teaching; Englisch; Fachsprache; Sprachunterricht; Electronic books